2021
DOI: 10.21273/hortsci15668-21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Volatile Compounds Produced by Selected Bacterial Endophytes in Promoting Plant Growth

Abstract: Bacterial endophytes selected for their capability to suppress diverse fungal pathogens in vitro and in greenhouse studies have been shown to promote plant growth. The effect of volatile compounds emitted by selected bacteria on plant growth in Arabidopsis thaliana, tomato (Solanum lycopersicum), sweet pepper (Capsicum annuum), and cucumbers (Cucumis sativus) was evaluated on container-grown plants nested above bacterial cultures, with roots exposed to the volatiles without direct contact between bacterial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Studies have shown that biochar plus PGPMs can improve soil quality and nutrient availability through activation of beneficial soil enzyme activity in tree plantations [ 117 ]. There is evidence that volatile organic compounds (VOCs) released by bacterial cells, including Bv , can induce increased growth in certain crops [ 118 ]. Other potential mechanisms for increased plant growth and health status with biochar and Bacillus biofertilizers include beneficial nutrient immobilization and release cycles triggered by microbial activity [ 74 ], pH and soil moisture changes [ 61 ], disease suppression by Bv [ 77 , 119 ], production of antibiotic lipopeptides by Bv [ 120 , 121 ], successful colonization by PGPMs of substrates via lipopeptide and biofilm production [ 121 , 122 ], and iron-chelating siderophore production in Bv [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that biochar plus PGPMs can improve soil quality and nutrient availability through activation of beneficial soil enzyme activity in tree plantations [ 117 ]. There is evidence that volatile organic compounds (VOCs) released by bacterial cells, including Bv , can induce increased growth in certain crops [ 118 ]. Other potential mechanisms for increased plant growth and health status with biochar and Bacillus biofertilizers include beneficial nutrient immobilization and release cycles triggered by microbial activity [ 74 ], pH and soil moisture changes [ 61 ], disease suppression by Bv [ 77 , 119 ], production of antibiotic lipopeptides by Bv [ 120 , 121 ], successful colonization by PGPMs of substrates via lipopeptide and biofilm production [ 121 , 122 ], and iron-chelating siderophore production in Bv [ 74 ].…”
Section: Discussionmentioning
confidence: 99%